2018
DOI: 10.11604/pamj.2018.29.227.15316
|View full text |Cite
|
Sign up to set email alerts
|

First documented evidence of dengue and malaria co-infections in children attending two health centers in Yaoundé, Cameroon

Abstract: To date, only a few cases of malaria and dengue co-infections have been reported around the world. We describe for the first time in Cameroon, concurrent infections among children (2 to 10 years) in two health centers of Yaoundé. The two dengue strains isolated in Cameroon clustered with the Asian II genotype. Although acute concurrent infections were benign, special attention should be given to malaria and dengue co-infection in order to prevent possible severe cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 6 publications
(6 reference statements)
3
35
0
2
Order By: Relevance
“…The frequency of dengue cases/malaria co-infections in our study was 13% (3/23) which is close to the 12.50% (3/24) observed in 2012/2013 in febrile patients in two hospitals of the capital city of Yaoundé, Cameroon [ 23 ]. Ayorinde et al .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The frequency of dengue cases/malaria co-infections in our study was 13% (3/23) which is close to the 12.50% (3/24) observed in 2012/2013 in febrile patients in two hospitals of the capital city of Yaoundé, Cameroon [ 23 ]. Ayorinde et al .…”
Section: Discussionsupporting
confidence: 82%
“…It is the second study that reports cases of dengue/malaria co-infection after the one conducted from 2012 to 2013 in the city of Yaoundé, Cameroon after testing retrospectively malaria positive cases [ 23 ]. The objective of this study was to determine the frequency of detection of DENV, ZIKV and CHIKV acute infections in febrile patients consulting at the New-Bell District Hospital in Douala.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the presence of DENV-Ab immunocomplexes is likely to influence TLR2/CD14-mediated responses 60 . Lastly, considering the role of TLR2 and TLR4 in detecting bacterial PAMPS, it will be important to address the effect of common co-morbidities including bacterial and parasitic co-infections or microbial translocation 6,7,74,75 , on DENV pathogenesis and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…During the past decade, there has been a rise of dengue cases in urban foci in Central Africa notably in Cameroon [26][27][28][29]. Even suspected, vectors were not well identified and characterised.…”
Section: Discussionmentioning
confidence: 99%
“…albopictus was identified as the main vector during concurrent dengue/chikungunya outbreak in Gabon in 2007 [8,22], and in Cameroon in 2006 [23]. During the last two decades, DENV-1 and DENV-2 mainly, were circulating in Cameroon [24][25][26][27][28][29]. Nationwide surveillance of dengue in 2006/2007 only revealed that seroprevalence (IgG and IgM antibodies) was higher in Douala [29].…”
Section: Introductionmentioning
confidence: 99%